7h-6=2h-21

Simple and best practice solution for 7h-6=2h-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7h-6=2h-21 equation:


Simplifying
7h + -6 = 2h + -21

Reorder the terms:
-6 + 7h = 2h + -21

Reorder the terms:
-6 + 7h = -21 + 2h

Solving
-6 + 7h = -21 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
-6 + 7h + -2h = -21 + 2h + -2h

Combine like terms: 7h + -2h = 5h
-6 + 5h = -21 + 2h + -2h

Combine like terms: 2h + -2h = 0
-6 + 5h = -21 + 0
-6 + 5h = -21

Add '6' to each side of the equation.
-6 + 6 + 5h = -21 + 6

Combine like terms: -6 + 6 = 0
0 + 5h = -21 + 6
5h = -21 + 6

Combine like terms: -21 + 6 = -15
5h = -15

Divide each side by '5'.
h = -3

Simplifying
h = -3

See similar equations:

| 2p+3=p-4 | | 123+3= | | 2p+3=-4 | | 8x+5=14-x | | 5+6x=25+x | | 12-6=8p-2 | | 7d=-2-18 | | 3a=20-2a | | 7d-2=-2 | | 4y-7=-3 | | 2(x-3)+5(x+2)=4(x-1)+3 | | 4m+1=-3 | | 4-3(2x+5)=5-(x-3) | | 12x+y=16 | | 2(x+21)=5x+21 | | 3(x+2)+2x=5x-2(x-4) | | 40-3x=17x | | 12p-6=8p-2 | | 4x+3x-4=3x+8 | | 7h+4=4h-5 | | 8x-2x+4=2x | | [10(3*x)+x]+[3x+10x]=88 | | 7d=-2d-18 | | 9x^2-225= | | 2x(2x-10)=-30+6x | | 2x-5(4-x)+3=14-(-5+2x) | | (2x^2+5x)(20x^2-7x-3)=0 | | 2y(y-1)=3-y | | 5(x+5)(x-10)=2(2.5x*x-1.9) | | 48=-8w | | 5(x+5)(x-10)=8.7 | | 9=2x-4 |

Equations solver categories